ANALISIS BIAYA BAHAN BAKU, BIAYA TENAGA KERJA LANGSUNG, BIAYA OVERHEAD PABRIK SEBAGAI ALAT PENGENDALIAN BIAYA PRODUKSI PADA USAHA JENANG TRADISIONAL BAROKAH DI DESA BONO KECAMATAN BOYOLANGU - Suciati, Diah; Pravitasari, Dyah (ITB AAS INDONESIA, 2024)
Production costs are the total costs borne by a company in producing a product. Production costs are the basis for every company in maintaining the company so that it does not experience losses. Losses will result in the company never growing and can stop the company's production activities. Therefore, it is very important to minimize these losses by keeping production costs under control. Cost control is one of the efforts that a company can make so that it can run successfully and efficiently. This research uses a qualitative approach method, with descriptive research type, using primary data and secondary data. The results of this research indicate that business cost management is a powerful option for increasing company revenue by minimizing production costs incurred during the product design process. In this way, production costs will be reduced, the selling price of the goods produced can compete with other companies, and the desired profits will be achieved ideally.